Sickness absence and disability pension in relation to first childbirth and in nulliparous women according to occupational groups: a cohort study of 492,504 women in Sweden - Charlotte Björkenstam; Krisztina D. László; Cecilia Orellana; Ulrik Lidwall; Petra Lindfors; Margaretha Voss; Pia Svedberg; Kristina Alexanderson (BMC, 2020)
Abstract Background Childbirth has been suggested to increase sickness absence (SA) and disability pension (DP). This may vary by occupation; however, knowledge in this field remains limited. We explored SA and DP in the years before and after childbirth among women in four occupational groups and those without occupation. Methods We studied nulliparous women aged 18-39 years, living in Sweden on December 31, 2004 (n = 492,504). Women were categorized into five skill-level based occupational groups and three childbirth groups; no childbirths within 3 years (B0), first childbirth in 2005 with no childbirth within 3 years (B1), and first childbirth in 2005 with at least one more birth within 3 years (B1+). We compared crude and standardized annual mean SA (in spells> 14 days) and DP net days in the 3 years before and 3 years after first childbirth date. Results Women in the highest skill level occupations and managers, had less mean SA/DP days during most study years than women in the lowest skill level occupations group. In B1 and B1+, absolute differences in mean SA/DP, particularly in SA, among occupational groups were highest during the year before childbirth. DP was most common in B0, regardless of group and year. Conclusions We found that women's mean SA/DP days before and after first childbirth was higher with decreasing skill-level of the occupational group and these differences were most pronounced in the year before childbirth. DP was most common among women not giving birth, regardless of occupational group.